Effectiveness of dynamic gait exercises on glycemic control and mobility in older adults with diabetes - Diovin Derose Vianni; Subramanian S; Surya Vishnuram; Syed Abudaheer K; Abdel Razzaq Al Hadidi; Riziq Allah Mustafa Gaowgzeh; Ahmed Fekry Salman (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction Gait impairments and poor glycemic control are common in geriatric diabetic patients, leading to increased fall risk and reduced quality of life. Dynamic gait exercises have been proposed as a strategy to enhance gait stability and metabolic control, but their comparative effectiveness remains underexplored. Objective The objective of this research is to assess the outcomes of dynamic walking movement on walking ability and blood sugar control in older adults with diabetes and compare them with traditional exercise programs. Methodology A power analysis was used to identify randomized controlled studies with 60 participants (±=0.05, performance = 0.80, Cohen D = 0.8). Using computer-generated block randomization, The participants were divided into two groups: one group that engaged in dynamic gait exercises (n = 30) and another group that served as the control (n = 30). Group assignments were unknown in the results statistics and results. HBA1C values ​​and dynamic walking index (DGI) were assessed before and after the 12-week intervention. Quality of life was assessed based on subscale SF-12 physics (PCS-12) and mentality (MCS-12). Results The dynamic gait exercise group exhibited significant improvements in DGI scores (23.85 ± 1.87 vs. 18.62 ± 2.10, p ≤ 0.001). HbA1c levels decreased significantly (8.32% to 5.78%, p ≤ 0.001), indicating improved glycemic control. SF-12 scores also improved significantly, with PCS-12 increasing from 47.5 ± 6.2 to 61.8 ± 5.7 and MCS-12 from 50.3 ± 7.1 to 64.1 ± 6.5 (p ≤ 0.001). Discussion These findings align with studies demonstrating that task-specific gait training enhances neuromuscular coordination and glycemic regulation in diabetic populations. While prior research has shown the benefits of aerobic and strength-based training, this study suggests that dynamic gait exercises provide additional advantages by integrating postural adjustments and cognitive-motor engagement. Conclusions Dynamic gait exercises significantly improved gait stability, glycemic control, and standard of living in geriatric individuals with diabetes. These findings support the integration of dynamic gait training into rehabilitation protocols for enhanced functional mobility and metabolic health in older adults with diabetes.